The Lower Limb Tendinopathies Etiology, Biology and Treatment - Bisciotti, Giannicola; Volpi, Piero (Sports and Traumatology, 2016)
This book examines the subject of lower limb tendinopathy and is divided into two main parts: the first covers the general aspects of tendinopathy, while the second focuses on the specific condition in the lower limb. Each chapter has a clear structure: etiopathogenesis, clinical presentation, imaging, conservative and surgical treatment, and therapeutic indications, making it easy to read. Furthermore, the section on conservative treatment includes important practical application tools.